INSTALASI DAN OPTIMALISASI JARINGAN INTERNET DENGAN MENGGUNAKAN KABEL FO DI PT REGYNET DATA SOLUSINDO - Neva, Talitha Nirmala; Kharisma, Ivana Lucia; Kamdan, Kamdan (MAJU : Indonesian Journal of Community Empowerment, 2025)
This report discusses internship activities carried out at PT Regynet Data Solusindo, an internet service provider company based on fiber optic (Fiber to the Home/FTTH). The purpose of this internship is to apply the knowledge that has been obtained during lectures in the Informatics Engineering study program, especially in the field of computer networks. Students are directly involved in the process of installation, optimization, and troubleshooting of customer internet networks. The implementation methods used include observation, interviews, documentation studies, and direct participation. In practice, students learn to use various network devices such as ONT, ODP, OPM, and OTDR, and understand the technical flow from installation to activation of internet services. In addition to the technical aspects, this activity also provides an understanding of the importance of professional ethics and professionalism in the field. The results of this internship activity show that direct involvement in the world of work can strengthen students' understanding of the theories learned in class while increasing their readiness to face the industrial world.